PEMBUATAN ALAT BANTU PEMOTONGAN SARI KELAPA PADA INDUST'RI KECIL PBDESAAN - Hadi, Setya; -, Nurdjito (Universitas Negeri Yogyakarta, 2004)
Introduction.UD. Kencana Gading Gejay'an CondongCatur, begunhisworkin coconutbusiness, thanhe thoughttouse thewater of coconutas objectofhisbusiness too.Now, theproductionof decocoisnotenough for themarket, becauseheslices it withknife. It makesslowly.and theproductis notreguler in shapeandthesize.'Ihis prograrnhasan objectiveto rnake a slicedeviceto apiecesof decocotobe smallone regularly,clean,wealthl,.easr,'todo, and rapidly, sothe,partnerwillheable toraise hisproduct.ThisProgramoffers the slicernethodrvithelectrical slicedevice.Itrnay slicemore reguler,easy,quickly,and made of stainless steelsheet,theprocessesinclude:surveythe appropriatematerial,the size ofdecoco,the condition of'shop andwhatneededb.,'the shop, todesign theslicedevice. toplantheprocesses,togetready thematerialandthe tools,to makethe slicer.to testand to makeit morebetl.er,togetpartner'sopinions,and tocompletethe design.Conclusion. ThisProgram trelpsUD.KencanaGading togeta slicer: thatwillraisethe productofdecoco, frorn 250 to600kg inone da1,, in regulen size that isI .2cm, togainthe addedvalues Rp 1.919.775. inevery month. The slioer has; capacity1200kg ina day,poweredby electrical motor 0,25 hp, 1420 rpm, easyto handlingand tomaintenance.